2003
DOI: 10.1046/j.1440-1754.2003.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis: A review of 18 cases in childhood

Abstract: The investigation of choice for establishing the diagnosis of ADEM was MRI of the brain. Other investigations were seldom helpful in reaching the diagnosis. Early diagnosis and prompt treatment of ADEM will probably reduce morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 28 publications
1
53
0
14
Order By: Relevance
“…In our study, 36.4% had fever and headache and 18.2% of patients had loss of consciousness at admission. In another series Gupte et al (11) reported the most common presenting symptoms as ataxia, loss of vision and headache. Anlar et al (12) reported 46 patients with common symptoms and signs pertaining to the motor system and consciousness.…”
Section: Discussion and Review Of Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…In our study, 36.4% had fever and headache and 18.2% of patients had loss of consciousness at admission. In another series Gupte et al (11) reported the most common presenting symptoms as ataxia, loss of vision and headache. Anlar et al (12) reported 46 patients with common symptoms and signs pertaining to the motor system and consciousness.…”
Section: Discussion and Review Of Literaturementioning
confidence: 94%
“…In the absence of specific biologic markers, the diagnosis of ADEM is based on clinical and radiologic features. Cerebral MRI shows high signal lesions of the same age on T2-weighted images in the subcortical white matter, with or without involvement of the cerebellum, gray matter and spinal cord (10,11). Presentation and clinical course can be quite variable because of the distribution of lesions in CNS.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…The lack of ADEM diagnostic criteria in adults permitting a calculation of "conversion rate" for ADEM to MS is probably associated to a short observation period. our study is longest than the previously longest follow-up of patients with ADEM 3,4,29 In the present study we have evaluated 15 ADEM patients, eleven of them monophasic, three multiphasic (MDEM) and one with recurrent (RDEM) evolution. Two patients were pediatric.…”
Section: Discussionmentioning
confidence: 99%
“…Acute disseminated encephalomyelitis (ADEM) is a demyelinating disorder characterized by multifocal involvement of the central nervous system (CNS) white and gray matter and, in some cases, peripheral nervous system lesions [1][2][3][4][5] . ADEM can be defined as an acute or sub acute inflammatory or demyelinating event affecting multifocal areas of the CNS, with no detectable infectious agent or other cause; when this event follow a specific infection it is named post-infectious encephalomyelitis (PIEM) or, when associated to immunization is considered post-vaccination encephalomyelitis (PVEM) [6][7][8][9] .…”
mentioning
confidence: 99%
“…5,6 It is one of the many syndromes that can develop after vaccination or a microbial infection, and has a 2-to 30-day latency period. 3,7 The typical MRI appearance is of demyelinating lesions preferentially affecting white matter tracts in a periventricular distribution.…”
Section: Discussionmentioning
confidence: 99%